Penerapan Media Pembelajaran Powerpoint Dalam Meningkatkan Hasil Belajar Matematika di SMK Negeri 1 Aek Nabara Barumun - Nurhayati Pulungan; Nurdalilah; Susi Sulastri Lubis; Mohd. Arifin (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2023)
The research method used was classroom action research using two cycles carried out in the first semester with SPLDV material. The sample in this research was 36 students in class X Office Automation and Management at SMK Negeri 1 Aek Nabara. The class used as a sample is class X Office Automation and Management at SMK Negeri 1 Aek Nabara which will use Power Point media in learning. The results of the research show that the ability of students' learning outcomes in learning Mathematics through the PowerPoint media learning model for class , then increased to 88.55 in the